Efektivitas Solution Focused Brief Counseling untuk Meningkatkan Resiliensi Siswa yang Mengalami Broken Home - Ayunda, Utari; Yuline, Yuline; Putri, Amallia (Edu Berkah Khatulistiwa, 2025)
This study aims to determine the effectiveness of solution focused brief counseling in increasing the resilience of broken home students at SMP Negeri 1 Sungai Raya. The method used is pre-experimental with one group pretest-posttest design. The population in this study were seventh grade students who experienced broken homes with a sampling of 6 broken home students who were in the low resilience category. this study used an instrument in the form of a questionnaire to determine the level of resilience of broken home students before and after being given group counseling services SFBC approach. The results showed that the average resilience questionnaire score of broken home students before being given treatment was in the low category with an average percentage value of 50% and after being given treatment increased by 72% which was included in the moderate category. From the results of hypothesis testing using paired sample t-test obtained sig value. (2 tailed) 0.002 <0.05. Then H0 is rejected and Ha is accepted, which means that there is an increase in resilience in broken home students. It can be concluded that solution focused brief counseling is effective for increasing the resilience of broken home students at SMP Negeri 1 Sungai Raya.